Persistence and Plasticity in Conifer Water‐Use Strategies. Issue 2 (18th February 2020) - Berkelhammer, M.; Still, C. J.; Ritter, F.; Winnick, M.; Anderson, L.; Carroll, R.; Carbone, M.; Williams, K. H.
Abstract: The selective use of seasonal precipitation by vegetation is critical to understanding the residence time and flow path of water in watersheds, yet there are limited datasets to test how climate alters these dynamics. Here, we use measurements of the seasonal cycle of tree ring δ 18 O for two widespread conifer species in the Rocky Mountains of North America to provide a multi‐decadal depiction of the seasonal origins of forest water use. The results show that while the conifer tree stands had a dominant preference for use of snowmelt, there were multi‐annual periods over the last four decades when use of summer precipitation was preferential. Utilization of summer rain emerged during years with increased snowfall and tree growth, suggesting that summer rain enhanced the transpiration stream only during the periods of highest water use. We hypothesize this could be explained through shallowing of the root profile during wetter periods and/or through the influence of changing water table depths on the residence time of summer precipitation in the root zone. We suggest the tree ring proxy approach used here could be applied in other watersheds to provide critical insight into the temporal dynamics of plant water use that could not be inferred from short measurement campaigns. These data on the seasonal origins of forest water are critical for understanding forest vulnerability to drought, the processes that affect precipitation pathways and residence time in watersheds and the interpretation of tree ring proxy data. Key Points: Cellulose isotope ratios were used to reconstruct the reliance on snowmelt for two common conifer species in the southern Rocky Mountains The trees exhibited multi‐year periods of preferential use of snowmelt and low tree growth following low snowpack years During high snowpack periods, the trees showed enhanced growth and utilized summer precipitation to support their increased water demands